Gondang Burogong in the Pasir Pengaraian community: a study of denotative and connotative meanings - Idawati Arman; Armansyah Anwar (Gelar: Jurnal Seni Budaya, 2025)
This study examines Gondang Burogong in the Pasir Pengaraian community by analyzing the denotative and connotative meanings embedded in its musical practices and socio-cultural context. The background of this research stems from concerns about shifts in the meaning of traditional music due to social change and technological development, which have the potential to reduce the local values contained within it. The purpose of this study is to reveal the denotative meaning of Gondang Burogong as a musical structure and practice, as well as its connotative meanings formed through situational contexts and analogies in the lives of the supporting community. The research employs a qualitative approach, with data collected through observation, in-depth interviews with artists and traditional leaders, and analysis of musical texts and practices. The findings indicate that, denotatively, Gondang Burogongfunctions as an accompaniment for ritual activities and traditional entertainment with distinctive musical patterns. Connotatively, this music represents values of togetherness, balance, and social order, which are interpreted situationally and analogically by the Pasir Pengaraian community. This study contributes to the enrichment of ethnomusicological and musical semiotic studies by offering a more comprehensive understanding of the relationship between musical texts and cultural meaning, and it has implications for efforts to preserve and revitalize traditional music based on local interpretations.